Carut-Marut Izin Pemasangan Reklame di Kota Makassar - Anisah Daeng Tarring (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
Child care is basically the responsibility of both parents. This includes various things: economic problems, education and everything that becomes the basic needs of children. The method used is juridical normative research. The results showed the position of custody of children after the divorce lived in the Parepare Religious Court, namely divorced parents remain obliged to care for, protect, and finance the child until the child is an adult. And the judge's consideration in granting child custody in the Parepare Religious Court is based on Law No. 1 of 1974 on Marriage and compilation of Islamic law and also considers the ability of parents in caring for and child care and considering various factors for the best interests of the child.